Wojtyła’s Category of Participation and the Question of Common Good - Jasiński, Karol (Philosophy and Canon Law, 2021)
The author presents Wojtyła’s views on participation and its connections to the common good. The analysis consists of two parts. The first part outlines the concept of participation (coexistence and action together with other people in relation to the common good) and its various forms (solidarity and opposition, conformism and evasion). The second part presents views of the nature of common good found not only in liberal thought (common good as the expression of deliberation and the rights of the individual), and personalist thought (common good as the development of the person and its natural potentialities), but primarily in the work of Wojtyła himself (common good as personal self-fulfilment through coexistence and cooperation with others in relation to the conscience-discerned truth, elected in a free act). His reference point was also personalism, which stresses the inalienable dignity of the person in both the private and the social spheres of life.